Folic acid supplementation during pregnancy and postpartum depressive symptoms - Bárbara Heather Lutz; Iná da Silva dos Santos; Marlos Rodrigues Domingues; Joseph Murray; Mariângela Freitas da Silveira; Vanessa Irribarem Avena Miranda; Marysabel Pinto Telis Silveira; Sotero Serrate Mengue; Tatiane da Silva dal Pizzol; Andréa Dâmaso Bertoldi (Revista de Saúde Pública, 2023)
ABSTRACT OBJECTIVE To verify whether folic acid supplementation during pregnancy is associated with the occurrence of maternal depressive symptoms at three months postpartum, in the 2015 Pelotas Birth Cohort. METHODS This study included 4,046 women, who were classified into three groups: did not use folic acid supplementation during pregnancy; used during only one trimester of pregnancy; and used for two or three trimesters. Depressive symptoms were assessed at three months postpartum using the Edinburgh Postnatal Depression Scale (EPDS), at cutoff points ≥ 10 (mild symptoms) and ≥ 13 (moderate to severe intensity). RESULTS The overall prevalence of mild symptoms was of 20.2% (95%CI 19.0–21.5), and moderate and severe was 11% (95%CI 10.0–12.0). The prevalence of EPDS ≥ 10 was of 26.8% (95%CI 24.0–29.5) among women who did not use folic acid and 18.1% for both those who used it during one trimester of pregnancy (95%CI 16.1–20.1) and those who used it for two or three trimesters (95%CI 16.0–20.2). The prevalence of EPDS ≥ 13 was of 15.7% (95%CI 13.5–17.9) in those who did not use folic acid, 9.1% (95%CI 7.5–10.6) in those who used it for one trimester, and 9.4% (95%CI 7.8–11.0) in those who used it for two or three trimesters. In the adjusted analyses, there was no statistically significant association between the use of folic acid during pregnancy and the occurrence of depressive symptoms at three months postpartum. CONCLUSION There was no association between folic acid supplementation during pregnancy and postpartum depression at three months.